2010
DOI: 10.1097/yic.0b013e328333ac1b
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of valproate versus lithium in mania or mixed mania: a randomized, open 12-week trial

Abstract: The objective of this study was to compare the efficacy and safety of valproate and lithium in bipolar I patients experiencing a manic or a mixed episode. This international, randomized, open-label, parallel-group, equivalence study included 268 patients with bipolar I disorder. The starting dose of valproate was 20 mg/kg/day and that of lithium was 800 mg/day. Treatment duration was 12 weeks. The primary outcome measure was mean change in Young Mania Rating Scale score between baseline and study end. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 21 publications
1
39
0
2
Order By: Relevance
“…The efficacy of lithium and divalproex in the management of acute mania is Yatham et al well established (level 1) (1-3). Two large, 12-week, open, randomized trials comparing lithium to divalproex found comparable efficacy and tolerability of these agents for the treatment of acute mania (46,47).…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 99%
“…The efficacy of lithium and divalproex in the management of acute mania is Yatham et al well established (level 1) (1-3). Two large, 12-week, open, randomized trials comparing lithium to divalproex found comparable efficacy and tolerability of these agents for the treatment of acute mania (46,47).…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 99%
“…Several studies have shown the comparable efficacy and safety of lithium and valproate 10,11 . The sustained antimanic activity of valproate in bipolar disorder [10][11][12] was further confirmed by the VALID study, which showed that valproate and lithium have comparable efficacy and tolerability in the treatment of acute mania over 12 weeks 13 .…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, published studies to date have largely been limited to North American populations [14][15][16] . To extend these observations to other populations, the VALID study was performed in six Eastern European and South East Asian countries to compare the effectiveness of valproate and lithium treatment in bipolar disorder 13 . The current study was designed as a pragmatic trial in order to determine medical costs in conditions which closely resembled standard clinical practice and would therefore be broadly generalisable.…”
Section: Introductionmentioning
confidence: 99%
“…One such RCT comparing aripiprazole, lithium and placebo in BP-I patients with mania or mixed episodes found both lithium and aripiprazole groups had significantly greater improvement compared with placebo after 3 weeks [18]. In another RCT comparing lithium, quetiapine and placebo in mania (n = 302) (excluding mixed episodes) lithium was superior to placebo in both short-and long-term Lithium was superior to placebo in treating mania [16] Yildiz et al [20] Kushner et al [21]. Similarly, another 12-week open randomized parallel group study comparing lithium and valproate in mania found both medications had high response and remission rates with comparable efficacy [22].…”
Section: Lithium Compared With Placebomentioning
confidence: 96%
“…Metabolic effects have been evaluated as outcomes in several studies [19,21,22,24,45-47]; however, one RCT was found specifically addressing metabolic effects. The year-long doubleblind RCT found lithium and aripiprazole had a similar metabolic profile in BP-I patients with a modest increase in body weight, but those with a lower BMI (<25) gained more weight on aripiprazole (p = 0.02) [104].…”
Section: Metabolic Effectsmentioning
confidence: 98%